Agronomic performance and severity of common rust in maize under different nitrogen sources - Pereira, Hélcio Duarte; Von Pinho, Renzo Garcia; Fiorini, Ivan Vilela Andrade; Resende, Ewerton Lélys; Resende, Felipe Ribeiro; Pires, Luiz Paulo Miranda (Revista Agrogeoambiental, 2020)
Nitrogen is the most required and complex management element in maize crop, promoting the highest responses in crop yield. The objective of this work was to verify the effect of different N sources on topdressing in minimum tillage and conventional tillage systems on the agronomic performance of the Pioneer 32R22YHR single cross and on the severity of common rust disease. Two experiments were carried out in a randomized block design (DBC) in the 2013/14 crop in minimum tillage and conventional tillage systems. The treatments were: control without nitrogen, ammonium sulfate, urea, ammonium nitrate, a physical mixture of nitrate (70%) and ammonium sulfate (30%) and a chemical mixture of these same sources in the same proportion just explained. Nitrogen sources had no significant effect on plant height, ear insertion height, ear prolificacy, grain yield and leaf severity of common rust, regardless of the sowing system. Under conventional tillage, the plants presented higher plant height, ear insertion and grain yield. There was no effect of sowing systems on prolificacy. With the exception of nitrogen free treatment, for all others, the severity of common rust was higher in minimum tillage system.